2023
DOI: 10.1007/s40617-023-00824-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Televisibility and Harm Probability on Clinical-Ethical Decision Making

Abstract: Researchers have recently begun to use a behavioral economics framework to study the clinicalethical decisions made by practicing behavior analysts. Much of this work, however, has examined broad patterns as opposed to isolating the underlying behavioral processes. In this study, we sought to extend past research by studying how clinical-ethical decisions would be influenced by a parametric manipulation of the probability that each available option would be televisible or cause short-term harm to the client. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Across both studies in Cox (2021), the researcher also found that what people claimed as the right thing to do (descriptive ethical behavior) appeared functionally distinct from why they claimed it was the right thing to do (normative ethical behavior); a finding that has been challenged for replicability and relevance to clinical-ethical choice in behavior analysis (Bailey, 2021). Cox and Javed (2023a) extended the above work by examining the role of probability discounting in ethical decision-making at the individual level. These researchers recruited 15 practicing behavior analysts and 30 non-behavior analysts.…”
Section: Probability Matching and Ethical Theory Preferencementioning
confidence: 88%
See 1 more Smart Citation
“…Across both studies in Cox (2021), the researcher also found that what people claimed as the right thing to do (descriptive ethical behavior) appeared functionally distinct from why they claimed it was the right thing to do (normative ethical behavior); a finding that has been challenged for replicability and relevance to clinical-ethical choice in behavior analysis (Bailey, 2021). Cox and Javed (2023a) extended the above work by examining the role of probability discounting in ethical decision-making at the individual level. These researchers recruited 15 practicing behavior analysts and 30 non-behavior analysts.…”
Section: Probability Matching and Ethical Theory Preferencementioning
confidence: 88%
“…Ethical gains were framed as behavior that complies with the participant's personal morals and ethics; and ethical losses were framed as behavior that violates the participant's personal morals and ethics. Past research has found that behavior analysts and non-behavior analysts alike will discount probabilistic ethical outcomes (Cox & Javed, 2023a). Thus, 5-trial adjusting probability tasks were used given their efficiency in obtaining an indifference point that can be used to generate a rate of ethical probability discounting.…”
Section: Methodsmentioning
confidence: 99%
“…For example, researchers have asked about standard assessment practices such as practitioners' use of functional assessment methodologies (Oliver et al, 2015;Roscoe et al, 2015) and their use of preference and reinforcer assessments (Graff & Karsten, 2012). As another example, researchers have asked about how services are delivered such as task interspersal (Bottini et al 2019) and the variables that influence clinical and ethical decisions (e.g., Cox & Brodhead, 2021;Cox & Javed, 2023;Kelly et al, 2023;Saini et al, 2018;Vanselow et al, 2011).…”
Section: Initial Description Of 39 Million Unique Aba Sessionsmentioning
confidence: 99%